Analisis Nilai Akidah dalam Kitab Pedoman Hidup di Alam Minangkabau Karya Syekh Sulaiman Arrasuli - Atiqah Zulfa Rahayu; Riza Wardefi (Prodi Pendidikan Keagamaan Islam, 2026)
This study investigates the Islamic creed values contained in Pedoman Hidup di Alam Minangkabau, a classical Minangkabau text written by Syekh Sulaiman Arrasuli. Using a qualitative descriptive content analysis approach, this research explores how the text integrates Islamic teachings with Minangkabau traditional wisdom. Data were collected through documentation and analyzed through reduction, categorization, and interpretation. The findings reveal several core values of Islamic creed emphasized in the text, including obedience in worship, sincerity in performing deeds, steadfastness and patience in facing life's trials, the cultivation of remembrance of Allah, and the integration of faith into social and cultural life. The study concludes that the text serves as an essential reference for understanding how Islamic values are harmonized with Minangkabau customs and provides relevant insights for Islamic education today.